BIBLIOMETRIC ANALYSIS OF THRIFTING RESEARCH IN MARKETING MANAGEMENT: MAPPING INTELLECTUAL STRUCTURE AND FUTURE RESEARCH AGENDA - Nur Eli Zayati; Suharto; Rachmad Ilham (Journal Informatic, Education and Management (JIEM), 2026)
This study maps the development of thrifting research in marketing management using quantitative bibliometric analysis on the Scopus database for the period 2015-2025. Quantitative methods are used to statistically measure publication trends , researcher productivity , and research structure . The results show significant growth since 2020 with an average of 23.5 percent per year . Four dominant themes were identified : consumer behavior , marketing strategy , environmental sustainability , and digital business models. The United States dominates with 32.4 percent of publications , while Indonesia only has 1.8 percent . Thrifting consumers prioritize product uniqueness over price. Knowledge gaps include a lack of research from the perspective of business actors . This study provides a statistical data -based map as a reference for future research development .